2016
DOI: 10.2139/ssrn.2765552
|View full text |Cite
|
Sign up to set email alerts
|

US Dollar Carry Trades in the Era of 'Cheap Money'

Abstract: In this paper, we employ a unique dataset of actual US dollar (USD) forward positions against a number of currencies taken by so-called commodity trading advisors (CTAs). We investigate the extent to which these positions exhibit a pattern of USD carry trading or other patterns of currency trading over the recent period of ultra-loose US monetary policy. Our analysis indeed shows that USD positions against emerging-market currencies are characterised by a pattern of carry trading. That is, the US dollar, as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…Another model with carry traders, fundamentalists, and chartists is proposed and the interactions between chartists and carry traders are part of the explanation of the forward premium puzzle has been demonstrated in [8], which contradicts the results in [10]. In line with the heterogeneous agent model developed in [8], a private data set was used to study the returns of carry trade strategies for emerging and developed markets, and it is found that carry trade strategies are not significant regressors for the Mexican peso during the Great Recession [54]. It is noted that the heterogeneous agent model with carry traders helps explain the puzzles of carry trading profits and exchange rate disconnects, as well as the microstructure of the market in terms of aspects such as the interactions between heterogeneous agents [14].…”
Section: Heterogeneous Agentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Another model with carry traders, fundamentalists, and chartists is proposed and the interactions between chartists and carry traders are part of the explanation of the forward premium puzzle has been demonstrated in [8], which contradicts the results in [10]. In line with the heterogeneous agent model developed in [8], a private data set was used to study the returns of carry trade strategies for emerging and developed markets, and it is found that carry trade strategies are not significant regressors for the Mexican peso during the Great Recession [54]. It is noted that the heterogeneous agent model with carry traders helps explain the puzzles of carry trading profits and exchange rate disconnects, as well as the microstructure of the market in terms of aspects such as the interactions between heterogeneous agents [14].…”
Section: Heterogeneous Agentsmentioning
confidence: 98%
“…The carry trade strategy also represents the magnitude of the forward premium, and the reduction in the profits of carry traders with increasing investment size causes the forward premium anomaly to disappear [10]. Carry trade returns, which have been proven to have long-range dependence in developed markets, can be explained mostly by the risk factors related to the foreign exchange market and have predictive power with other contemporaneous drivers, such as interest rate differentials and foreign exchange rate volatility [53][54][55][56]. By comparing a portfolio based on expectations with trend and carry trade portfolios, it is found that carry trade strategies become less profitable with low interest rate differentials and note that the time-varying characteristic of monetary policy affects expectations [57].…”
Section: Heterogeneous Agentsmentioning
confidence: 99%
“…Mishra et al (2014),Nechio (2014),Aizenman et al (2016),Eichengreen and Gupta (2015),Kim (2015) argue that in the wake of the global financial crisis high-yielding emerging markets were promising investment destinations, and that they were subject to waves of carry trade flows through the global search for yield.14 Shehadeh et al (2016) analyze a data set of US dollar forward positions against several developed and developing country currencies taken by Commodity Trading Advisors (CTAs) over the period followed the financial crisis. They find evidence on carry trade pattern for developing market currencies but not for developed market ones.…”
mentioning
confidence: 99%